Systematic review of the use of phytobiotics in broiler nutrition - Deminicis, Renata Gomes da Silveira; Meneghetti, Camila; Oliveira , Elizângela Bonfim de; Garcia Júnior, Antônio Amândio Pinto; Farias Filho, Ronaldo Vasconcelos; Deminicis, Bruno Borges (Revista de Ciências Agroveterinárias, 2021)
The objective of this study was to conduct a systematic review of the literature on the use of phytogenics in broiler nutrition. A bibliographic survey was conducted for the years between 2009 and 2019, using the keywords “eubiotics,” “phytobiotics,” “essential oils,” “phytogenic extracts,” and corresponding words associated with the terms “broiler” and “poultry.” The selected articles were grouped into the categories: animal performance, histomorphology of the intestinal wall, biochemical profile, carcass characteristics, and the effect on bacteria found in the intestine. After comparisons of several parameters on the use or non-use of phytogenics, it was found that replacing antibiotics with phytogenics contributes positively to performance, the histomorphology of the intestinal wall, the biochemical profile, carcass characteristics, and the number of bacteria found in the gut. In conclusion, based on several studies found in the literature, replacing antibiotics with phytogenic additives in broiler nutrition may be viable due to their lower residual impact on the final product, in addition to their positive effect on the parameters of animal production.